A STUDY ON VALUE CHAIN ANALYSIS OF CASTOR IN SALEM AND NAMAKKAL DISTRICT, TAMIL NADU - Venkatesa Palanichamy N,; Subhashree M,; Kalpana M,; Balakrishnan N, (The Bioscan, 2024)
Oilseed crops are the second most important agricultural product after cereals, accounting for 14% of total planted land. These oilseeds are mostly grown in rainfed conditions and provide a source of income for small and marginal farmers in the country's arid and semi-arid habitats. Castor is a commercially significant plant across the world. Castor may have evolved in the tropical regions of both India and Africa. This study was conducted in the Salem and Namakkal district of Tamil Nadu. These districts were chosen purposively because they were largest castor producing districts in Tamil Nadu. Five villages were chosen from each block, with five sample farmers chosen from each village, to carry out the research. Thus, the total sample size of the farmers accounted to 100. Data were collected from the sample farmers and other value chain actors by personal interviews with the assistance of a comprehensive interview schedule. The statistical techniques like percentage analysis, cost and returns, price spread analysis and Garrett ranking technique were used. Results showed that majority of sample farmers (49 per cent) were of 35 to 50 years of age; 64 per cent had the secondary education; 91 per cent of the respondents had agriculture as their main occupation; 49 per cent of the farmers had small land holding; 49 per cent of farmers earned between Rs.1 to 2 lakhs; 64 percent of the farmers had 15-30 years of experience. And 41-50 aged intermediaries predominantly involved in castor marketing and value addition; experienced intermediaries involved in marketing of castor.